Factors affecting clay dispersion in oxisols treated with vinasse - Thadeu Rodrigues de Melo; Tiago Santos Telles; Walquiria Silva Machado; João Tavares Filho (Semina: Ciências Agrárias, 2016)
Vinasse is a potassium-rich waste generated in large amounts by the ethanol production that, applied in the soil, can promote changes in water dispersible clay and in its physical quality. The aim of this study was to evaluate the clay dispersion of Oxisols after vinasse application and correlate it with some chemical attributes. Samples were collected in two Oxisols (155 and 471 g of clay kg-1), put in pots, received dosages of vinasse (0, 50, 100, 150 and 200 m3 ha-1) and remained incubated during 120 days. Phosphorous, organic carbon, pH H2O, pH KCl, pH CaCl2, Al3+, H+Al3+, Ca2+, Mg2+, K+, Na+, Delta pH and the proportion between monovalent and bivalent cations have been evaluated and correlated with the clay flocculation degree. Vinasse changed almost all chemical variables in both soils and increased the flocculation in the sandy soil, but did not change the clayey one. Delta pH, Mg2+ and K+ significantly correlated with the flocculation degree in the sandy soil. It is possible to conclude that the dispersive effect of K+ added by vinasse are irrelevant, considering the flocculant effect caused by the increment in Mg2+ and Delta pH after vinasse application.